Menumbuhkan Sikap Kepemimpinan Sejak Dini Kelas VI Sekolah MI-Al Amin Pa’batangan Kabupaten Takalar Kecamatan Mappakasungguh - Ela, Ela; Risnanosanti, Risnanosanti; Yusmaniarti, Yusmaniarti (Jurnal Dehasen Mengabdi, 2023)
Leadership is the responsibility of everyone including elementary school children. The most important contribution for any educator is identifying and developing leadership attitudes in children. Elementary school teachers have the opportunity to instill leadership in the classroom, the importance of instilling and honing leadership from an early age aims to prepare the best generations for the future. Generation that will replace the older generation to continue the task of filling independent and development. Generation that is ready to face any challenges that will come in the future. Regarding how to foster leadership attitudes in children so that they gin experience and learning and can internalize leadership attitudes from an early age.